دراسة تجريبية للخواص الفيزيائية للديود الليزري (AlGaAs/GaAs) لاستخدامه كمنبع ضخ لليزر Nd:YAG (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
البحث يتضمن دراسة تجريبية للخواص الفيزيائية للديود الليزري ( زرنيخ غاليوم الألمنيوم)، حيث قدمنا عرضًا تفصيليًا لبنية الديود وآلية عمله, وكذلك ملاءمته كمنبع ضخ لليزر الحالة الصلبة Nd:YAG . ثم درسنا تحولات فرق الكمون ( المعبر عن استطاعة الديود الليزري) بتابعية درجة حرارة الديود, وذلك من أجل شدات مختلفة لتيار الحقن, و تغيرات الكمون بتابعية تيار الحقن, وأخيراً قمنا بدراسة استطاعة خرج الديود الليزري بتابعية تيار الحقن.   The research includes an experimental study of the physical properties of the laser diode (AlGaAs/GaAs): We have made a detailed display of the structure of diode and mechanism of its operation, as well as its convenience as a pumping source for Solid-state laser Nd:YAG. Then we studied the changes of potential difference (expressing the capacity of laser diode) by the dependence of diode temperature, for variant intensity of the injection current, and the changes of potential by dependence of the injection current; and finally, we made a study of the capacity of laser diode output by dependence of the injection current.